Studies in law, politics, and society. Vol. 35 - Sarat, Austin (Bingley, U.K. : Emerald, 2005)
This volume of "Studies in Law, Politics, and Society" presents a diverse array of articles by an interdisciplinary group of scholars. Their work spans the social sciences, humanities, and the law. Those scholars examine the nature of family and the intersection of family and law, the way contexts shape legal actors, and the nature of rights and resistance. The articles published here exemplify the exciting and innovative work now being done in interdisciplinary legal scholarship.
Judging knowledge : the court as arbiter of social scientific knowledge and expertise in LGBT custody and adoption cases / Kimberly D. Richman -- Fathers' rights, feminism and Canadian divorce law reform : 1998-2003 / Ruth M. Mann -- Anatomy of Hollywood's hero-lawyer : a law-and-film study of the western motifs, honor-based values and gender politics underlying anatomy of a murder / Orit Kamir -- Unreasonable doubt : manipulating jurors' perceptions in a closing argument at trial / Pamela Hobbs -- When rights collide : anti-abortion protests and the ideological dilemma in planned parenthood Shasta-Diablo, Inc. V. Williams / Joshua C. Wilson -- Communication, power, and critique : toward a critical theory of everyday resistance / Glenn Mackin.
Print version record
Keywords: Law -- General; Political Science -- History & Theory; Jurisprudence & general issues; Politics & government; Sociological jurisprudence; Political sociology; Law -- Political aspects